Myanmar : Second Review Under the Staff-Monitored Program. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper reviews Myanmar's Second Review Under the Staff-Monitored Program IMF staff report. The IMF report highlights that the authorities are pursuing a wide range of economic reform program against a background of political liberalization. Growth has strengthened led by services. However, international reserves remain low, and inflation pressures are significant. It suggests that fiscal policy needs to continue balancing stability with development, while administrative reforms to boost revenue and public financial management need to be driven forward.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet